International consensus statement: methods for recording and reporting of epidemiological data on injuries and illnesses in golf. Issue 19 (26th August 2020) - Murray, Andrew; Junge, Astrid; Robinson, Patrick Gordon; Bizzini, Mario; Bossert, Andre; Clarsen, Benjamin; Coughlan, Daniel; Cunningham, Corey; Drobny, Tomas; Gazzano, Francois; Gill, Lance; Hawkes, Roger; et al.
Abstract : Epidemiological studies of injury in elite and recreational golfers have lacked consistency in methods and definitions employed and this limits comparison of results across studies. In their sports-generic statement, the Consensus Group recruited by the IOC (2020) called for sport-specific consensus statements. On invitation by International Golf Federation, a group of international experts in sport and exercise medicine, golf research and sports injury/illness epidemiology was selected to prepare a golf-specific consensus statement. Methodological stages included literature review and initial drafting, online feedback from the consensus group, revision and second draft, virtual consensus meetings and completion of final version. This consensus statement provides golf-specific recommendations for data collection and research reporting including: (i) injury and illness definitions, and characteristics with golf-specific examples, (ii) definitions of golf-specific exposure measurements and recommendations for the calculation of prevalence and incidence, (iii) injury, illness and exposure report forms for medical staff and for golfers, and (iv) a baseline questionnaire. Implementation of the consensus methodology will enable comparison among golf studies and with other sports. It facilitates analysis of causative factors for injuries and illness in golf, and can also be used to evaluate the effects of prevention programmes to support the health of golfers.